Impact assessment of Benazir Nashonuma Programme (BNP) on maternal, child health and nutritional status in Pakistan: A quasi-experimental study protocol - Muhammad, Shah; Malik, Asma Abdul; Soofi, Sajid; Habib, Atif; Umer, Muhammad; Rizvi, Arjumand; Ahmed, Imran; Leroy, Jef L.; Cousens, Simon; Bhutta, Zulfiqar Ahmed (BMJ, 2025)
Introduction Maternal and child malnutrition is a significant public health concern in Pakistan, with 40% of children under five being stunted. In response, the Government of Pakistan initiated the Benazir Nashonuma Programme (BNP), a nutritional supplementation programme for pregnant women, mothers of children aged 0 to 23 months and children aged 6 to 24 months. This study aims to evaluate the effectiveness of the BNP in reducing childhood stunting and improving maternal and child health outcomes.